PEMANFAATAN TEPUNG SUWEG DAN TEPUNG KACANG MERAH DALAM PEMBUATAN SNACK BAR SEBAGAI ALTERNATIF MAKANAN SELINGAN PENDERITA DIABETES MELITUS - Aulia Adha Arzaqina (2020)
The prevalence of people with diabetes mellitus in Indonesia on 2018 is 2.0%. This can be handled by consuming foods with high-fiber, high-antioxidants, and low-glycemic index values. Elephant foot yam is a high-fiber and low-glycemic index food whose production is quite abundant with relatively low price. In addition, red beans have the benefit to increase the content of protein and antioxidants. This study aims to utilize local food products and determine the nutritional content, dietary fiber content, and sensory acceptance of snack bars made of elephant foot yam flour and red bean flour. In order to obtain the best formulation, the Completely Randomized Design (CRD) method with three different formulations and 30 panelists was used. Organoleptic test analysis used the method of Kruskal Wallis test and continued with the Mann-Whitney test. The results showed that the variations in the mixture of both elephant foot yam flour and red bean flour had a significant effect (p <0.05) on the taste level of snack bar texture. The snack bar F2 (50% elephant foot yam flour : 50% red bean flour) was the best formulation with the highest level of preference. The selected snack bar of F2 contains 22.79% water, 2.925% ash, 10.6625% protein, 11.4175% fat, 52.205% carbohydrate, and 17.725% dietary fiber. The recommended snack bar consumption for DM 1900 kcal is one bar for three meals.